(untitled) (Research, Society and Development, 2022)
Objective: To analyze the perception of caregivers of children and adolescents with a recent diagnosis of malignant neoplasia, under hospital treatment, regarding the practice of Hatha-yoga. Method: Fourteen caregivers who performed four to six integrative practices, applied individually, with 35 minutes duration, participated in the study, in a period ranging from four to fourteen days. A qualitative approach was used based on semi-structured interviews, audio-recorded and transcribed after the intervention period, and content analysis in the interpretation of the data. Results: Participants reported positive sensations and improvements in their psychophysical condition. Practicing Hatha-yoga allowed them: the acquisition of self-knowledge; the apprehension of philosophical and practical aspects in their lives; the unfolding of benefits to its related and the recognition of its relevance to the hospital oncology service. Conclusion: Hatha-yoga is a good reference for comprehensive health care, recommended for caregivers of children and adolescents with a recent diagnosis of cancer in hospital treatment.